Opinion de Sodarcan inc. concernant la taxe sur les produits et les services - Grenier, Gilles P. (Assurances)

(untitled) (HEC Montréal, 1990)
Sodarcan inc. supports the Government's initiative and commitment to replace the present federal sales tax by a value added tax known as the "Goods and Services Tax (GST)"; in principle, such a reform is preferable to the status quo. We, however, favour the introduction of a GST system which would reduce the administrative burden for companies and not unduly impair the profitability of property and casualty (P & C) insurance intermediaries. In addition, within this reform, the Government must not be deterred from the absolute necessity to better contrai its expenses and to hold back inflationary pressures on the Canadian economy. Sodarcan inc. asks that the Standing House Committee on Finance make the following recommendations to the Government of Canada: 1. Eliminate, from the GST system, the tax-exempt status for insurance brokerage, reinsurance brokerage and reinsurance underwriting operations, as they relate to P & C insurance. We are of the opinion that these operations should be taxed according to the same GST principles which apply to most commercial activities. However, some of the activities in the area of P & C insurance, such as those provided to individuals, could be zero-rated. 2. The introduction of specific terms of application which would enable related companies to regroup themselves for the purposes of the GST, such as the systems currently being used in France and in the United Kingdom, in view of avoiding a significant negative impact on the cash fiow and on the operating costs of the companies concerned and, in some cases, of avoiding double taxation. This request would become even more pressing if the Government of Canada were to keep P & C insurance tax-exempt, a status we request the Government eliminate, as outlined above. 3. The introduction of transitional rules, in the event the Government decides to keep the tax-exempt status for P & C insurance, providing for a reimbursement, in the form of credits, of the GST paid: a) on losses reinsured under P & C reinsurance treaties written prior to January 1, 1991; and b) on administrative costs incurred by reinsurance brokers and reinsurers for the settlement of fosses under P & C reinsurance treaties written prior to January 1, 1991. The basis of application for the GST which we recommend would: a) ensure fairness and respect for competitive positions; b) reduce the administrative burden on companies; c) not adversely affect the profitability of property and casualty intermediaries; and d) respect the fundamental objectives advanced by the Government in the White Paper on the reform of the sales tax to implement a neutral and visible GST system.